Thermogemmatispora aurantia sp. nov. and Thermogemmatispora argillosa sp. nov., within the class Ktedonobacteria, and emended description of the genus Thermogemmatispora. Issue 6 (4th April 2019) - Zheng, Yu; Wang, Chiung-Mei; Sakai, Yasuteru; Abe, Keietsu; Yokota, Akira; Yabe, Shuhei
Abstract : Two thermophilic, aerobic, Gram-stain-positive Ktedonobacteria strains, A1-2 T and A3-2 T, were isolated from geothermal soil in Japan. The strains formed orange-coloured colonies on 10-fold diluted Reasoner's 2A medium, followed by formation of branched aerial mycelium with multiple grape-like spores. Both strains hydrolysed casein, carboxymethyl cellulose, starch, chitin and xylan, but did not liquify gelatin. Strain A1-2 T utilised sucrose and gellan gum and was inhibited by inositol, while strain A3-2 T utilised only gellan gum and was not inhibited by inositol. The DNA G+C contents of strain A1-2 T and A3-2 T were 63.2 and 63.1 mol%, respectively. Chemotaxonomic data (major fatty acid, iso-C17 : 0 ; major menaquinone, MK-9(H2 ); cell-wall amino acids, ornithine, serine, glycine, glutamic acid, alanine and β-alanine; polar lipids, phosphatidylinositol, phosphatidylglycerol, diphosphatidylglycerol, one unidentified lipid, one unidentified phosphoglycolipid and three unidentified glycolipids; major cell-wall sugars, mannose, arabinose and xylose) indicate that both strains belong to the genus Thermogemmatispora . 16S rRNA gene sequence analysis indicated that strain A1-2  T was most closely related to the type strains of Thermogemmatispora onikobensis (97.7 % sequence similarity), and that strain A3-2 T was most closely related to the type strains of Thermogemmatispora carboxidivorans (97.2%), but DNA–DNA hybridization shows relatedness values of <67 % with previously described type strains. Moreover, 16S rRNA gene sequence similarity and DNA–DNA relatedness between strain A1-2 T and strain A3-2 T were 96.0 and 33.4%, respectively, suggesting that the two strains are genetically distinct. The two strains are proposed as Thermogemmatispora aurantia sp. nov. and Thermogemmatispora argillosa sp. nov.